Layered scenario mapping: a multidimensional mapping technique for collaborative design. Issue 3 (2nd July 2016) - Lurås, Sigrun
Abstract: Making use of insights gained through field research in design can be challenging. Some issues that design teams may face are making sense of fragmented data collected, sharing insight among the design team and presenting the data in ways that support the situated design work. This paper introduces layered scenario mapping, a technique aimed at meeting such issues when designing a ship's bridge. The technique builds on and expands traditional techniques for representing user data in design and results in a map describing a typical scenario along several dimensions and at different levels of abstraction. It highlights the spatial and temporal aspects of the situation, and emphasises the use of visual presentations. This paper describes why and how the layered scenario mapping technique was created, it critically assesses the technique and discusses experiences with using it. The technique proved to be valuable in making sense of fragmented data, and supported the design team's collaborative work when designing a ship's bridge. It is expected that the technique can also prove valuable when designing for other contexts where the spatial and/or temporal dimensions are of importance.